Bottlenecks in Adoption of Agroforestry Practices in Jammu Division of Jammu and Kashmir - S. K. Gupta; Khare V. Pushkar; P. S. Slathia; Rakesh Kumar (Indian Journal of Extension Education, 2022)
Agro-forestry is an excellent medium of land utilization for obtaining the maximum output. In both irrigated and rain-fed environments, agroforestry is practised to produce food, fuel, fodder, timber, fertiliser, and fibre. It also contributes to nutritional and ecological security, supports livelihoods, reduces poverty, and encourages resilient and productive cropping and farming environments. Adoption of different practices of agroforestry systems is very much crucial for sustaining the livelihood of resource poor farmers particularly in rainfed area. The present study was carried out in 10 blocks of Jammu district of Jammu and Kashmir in 2018 to identify different bottlenecks encountered by farmers in adoption of different agro-forestry practices. Multistage random sampling method was used for selection of 160 respondents from study area. The results show lack of awareness, lack of structural market and lack of interactions with respective governmental organizations were the major bottlenecks in adoption of different agroforestry practices for sustainable livelihood generation.